1,5, and 25. 1*25=25 and 5*5=25
Step-by-step explanation:
I think the fig.. will helps you a lot...
Answer:
![\frac{3}{13} + \frac{2i}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B13%7D%20%2B%20%5Cfrac%7B2i%7D%7B13%7D)
Step-by-step explanation:
The multiplicative inverse of a complex number y is the complex number z such that (y)(z) = 1
So for this problem we need to find a number z such that
(3 - 2i) ( z ) = 1
If we take z = ![\frac{1}{3-2i}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3-2i%7D)
We have that
would be the multiplicative inverse of 3 - 2i
But remember that 2i = √-2 so we can rationalize the denominator of this complex number
![\frac{1}{3-2i } (\frac{3+2i}{3+2i } )=\frac{3+2i}{9-(4i^{2} )} =\frac{3+2i}{9-4(-1)} =\frac{3+2i}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3-2i%20%7D%20%28%5Cfrac%7B3%2B2i%7D%7B3%2B2i%20%7D%20%29%3D%5Cfrac%7B3%2B2i%7D%7B9-%284i%5E%7B2%7D%20%29%7D%20%3D%5Cfrac%7B3%2B2i%7D%7B9-4%28-1%29%7D%20%3D%5Cfrac%7B3%2B2i%7D%7B13%7D)
Thus, the multiplicative inverse would be ![\frac{3}{13} + \frac{2i}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B13%7D%20%2B%20%5Cfrac%7B2i%7D%7B13%7D)
The problem asks us to verify this by multiplying both numbers to see that the answer is 1:
Let's multiplicate this number by 3 - 2i to confirm:
![(3-2i)(\frac{3+2i}{13}) = \frac{9-4i^{2} }{13} =\frac{9-4(-1)}{13}= \frac{9+4}{13} = \frac{13}{13}= 1](https://tex.z-dn.net/?f=%283-2i%29%28%5Cfrac%7B3%2B2i%7D%7B13%7D%29%20%3D%20%5Cfrac%7B9-4i%5E%7B2%7D%20%7D%7B13%7D%20%20%3D%5Cfrac%7B9-4%28-1%29%7D%7B13%7D%3D%20%5Cfrac%7B9%2B4%7D%7B13%7D%20%3D%20%5Cfrac%7B13%7D%7B13%7D%3D%201)
Thus, the number we found is indeed the multiplicative inverse of 3 - 2i